Rancangan Sistem Cari dan Temu Barang Hilang di Universitas Udayana Berbasis Web - Zerina Nur Salsabila; I Gusti Ngurah Anom Cahyadi Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
Losing items is an event that has been experienced by all of us. At Udayana University itself, loss of goods is still a common problem that is often faced by students, lecturers, and staff. This of course can result in material loss and inconvenience for the owner of the goods. Currently at Udayana University to disseminate information on the announcement of lost items is still by means of social media only. To overcome this problem, a web-based lost and found system was designed called